Learning from economic downturns : how to better assess, track, and mitigate the impact on the health sector - Hou, Xiaohui (Directions in development (Washington, D.C.). Human development., 2013)
Health and economic development are interconnected. Over the past decades, the health sector has become an increasingly important component of the global economy, evidenced by the growing trend of health expenditures as a share of GDP. The interconnectivity of health and economic development and the cyclical nature of economic performance have emphasized the critical need to build health sector resilience to prepare for inevitable economic downturns. The objective of the book is to raise awareness of the challenges that health systems, in both developing and developed countries, face in times of economic crisis and provide an Assessment, Tracking and Mitigation (A.T.M.) framework by which governments and policy makers can meet the critical challenge of health sector stabilization and resilience building. The A.T.M. framework emphasizes the importance of the interdependence of these three pillarsfor effective crisis response and strengthening health system resilience to economic shocks. -- Publisher description.